Ethnobotanical study of traditional forage plants in the Gansu-Ningxia-Inner Mongolia junction zone: conservation and sustainable utilization for animal husbandry - Jian Xie; Xiaoqi Liu; Mingxia Luo; Fusong Liu; Sha Liu; Yongxia Zhao; Xingsheng Zhang; Wenji Zhao; Faming Wu (BMC, 2023)
Abstract Introduction This study aims to safeguard the ethnobotanical knowledge pertaining to traditional forage plants within the ethnically diverse Gansu-Ningxia-Inner Mongolia junction zone. It seeks to establish a foundation for the sustainable utilization of these traditional resources for animal husbandry. Methods A combination of literature research, village interviews, participatory observation, and ethnobotanical quantitative evaluation methods was employed to investigate and study the traditional knowledge of wild forage plants used by local residents in the study area. Results Local residents provided information on 73 forage plants, which were identified as 116 distinct wild forage plant species. These plants belong to 22 families and play an active role in the lives of the local inhabitants. Notably, the families Poaceae, Fabaceae, and Asteraceae are prominent, comprising the most abundant and widely utilized wild forage plants. Bing Cao (collectively referring to plants of the Agropyron, Leymus, and Psammochloa), Suo Cao (collectively referring to plants of the genus Stipa), and Ku Cai (encompassing Lactuca tatarica (L.) C.A.Mey. and Ixeris polycephala Cass.) emerge as the most representative and vital wild forage plants for animal husbandry. Additionally, plants within the Astragalus (referred to collectively as NiaoZi by local residents) in the Fabaceae family, as well as plants from the Amaranthaceae family, exhibit notable significance. Conclusion Animal husbandry assumes a pivotal role in the local agricultural economy, and the 116 wild forage plants investigated hold substantial importance in its development. Among these, 59 and 103 plant resources display high developmental potential, making them prospective candidates for high-quality cultivated forage grasses. Additionally, extensive grazing practices have resulted in significant ecological degradation within this already fragile ecosystem. The cultivation of forage grasses and the practice of pen-based animal husbandry may emerge as crucial strategies for sustainable development in this area.